Production process of plastic magnetic pump body for electrolyte delivery

CN122956627APending Publication Date: 2026-10-23XIWO NEW ENERGY TECH (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611118353.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

而电解液挥发出的碳酸酯类有机溶剂蒸气具有易燃易爆特性,静电火花可能引发燃烧或爆炸等安全事故

Benefits of technology

1、本发明制备的电解液输送用塑料磁力泵泵体,以聚四氟乙烯为耐腐蚀基体,通过氮掺杂碳包覆碳纳米管与PFA-碳纤维复合粉体的协同引入,在保持材料耐电解液腐蚀的前提下,提高其抗静电性能与力学增强。其中,氮掺杂碳包覆碳纳米管经液相球磨预处理后分散于PTFE基体中,形成连续的导电通道,PFA-碳纤维复合粉体中的碳纤维承担主要机械载荷,提高基体承载能力,同时PFA组分在烧结温度下软化熔融,有助于填充聚四氟乙烯颗粒间隙并改善烧结坯体致密性,二者协同使泵体兼具静电安全泄放能力与结构承载性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1785135602878-000001
    Figure REF-OBJ-1785135602878-000001
Patent Text Reader

Abstract

The application discloses a production process of a plastic magnetic pump body for electrolyte delivery, belongs to the technical field of fluoroplastic processing, and comprises the following steps: in-situ forming a polypyrrole coating layer on the surface of carbon nanotubes by taking pyrrole as a monomer and ammonium persulfate as an oxidant, and then preparing nitrogen-doped carbon-coated carbon nanotubes through two-stage high-temperature calcination; simultaneously, preparing PFA-carbon fiber composite powder by melt blending polyperfluoroalkoxy resin and carbon fibers; then, pretreating the nitrogen-doped carbon-coated carbon nanotubes through ball milling dispersion, mixing the nitrogen-doped carbon-coated carbon nanotubes with polytetrafluoroethylene powder and the PFA-carbon fiber composite powder to obtain a composite mold pressing material, placing a metal framework subjected to surface roughening and anchoring treatment in a mold, filling the mold pressing material, cold-pressing and forming, sintering and annealing, and then machining to obtain the pump body. Through the synergistic effect of the nitrogen-doped carbon-coated carbon nanotubes and the PFA-carbon fiber composite powder, the antistatic performance and mechanical strength of the pump body are improved, and the use requirements of corrosion resistance, antistatic property and long-term operation stability for safe electrolyte delivery are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fluoroplastics processing technology, specifically the production process of a plastic magnetic pump body for electrolyte delivery. Background Technology

[0002] In the chemical production fields of lithium batteries and sodium batteries, electrolytes (such as lithium hexafluorophosphate-based electrolytes) typically contain highly corrosive lithium salts, carbonate organic solvents, and various additives, exhibiting strong chemical corrosivity to conveying equipment. Therefore, the equipment used for electrolyte conveying requires excellent corrosion resistance, sealing properties, and chemical stability. Plastic magnetic pumps, due to their seal-free and zero-leakage structure, are widely used in electrolyte conveying applications. Polytetrafluoroethylene (PTFE) exhibits excellent chemical corrosion resistance and good tolerance to hydrofluoric acid and carbonate solvents that may be produced by the decomposition of lithium hexafluorophosphate electrolytes. It is not prone to swelling or degradation and also has a wide operating temperature range. Therefore, it is often used as the base material for the pump body of plastic magnetic pumps used for electrolyte conveying.

[0003] However, polytetrafluoroethylene (PTFE) has an extremely high volume resistivity, making it a typical high-insulation material. During the high-speed flow of the electrolyte, intense friction occurs between the electrolyte and the inner wall of the PTFE pump casing, easily generating and accumulating a large amount of static charge. Since PTFE itself lacks the ability to discharge static electricity, the static charge continuously accumulates on the pump casing surface. When the charge density reaches a certain level, it can easily generate electrostatic discharge sparks. Furthermore, the carbonate organic solvent vapors emitted from the electrolyte are flammable and explosive, and these electrostatic sparks could potentially cause combustion or explosions, leading to safety accidents.

[0004] Therefore, how to synergistically improve the antistatic properties and mechanical strength of the pump body while maintaining the excellent corrosion resistance of polytetrafluoroethylene, and ensure the long-term stable operation of electrolyte safe delivery, is a core technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a manufacturing process for a plastic magnetic pump body for electrolyte transportation. By introducing nitrogen-doped carbon nanotubes as an antistatic modified filler and PFA-carbon fiber composite powder into polytetrafluoroethylene (PTFE), the conductive network formed by the nitrogen-doped carbon nanotubes after liquid-phase ball milling and dispersion, combined with the load-bearing and reinforcing effect of carbon fibers in the PFA-carbon fiber composite powder, and the softening and melting filling of PFA at sintering temperature, the antistatic performance and mechanical strength of the pump body are synergistically improved while maintaining the corrosion resistance continuity of PTFE, thus meeting the requirements for safe electrolyte transportation in terms of corrosion resistance, antistatic properties, and long-term operational stability.

[0006] The objective of this invention can be achieved through the following technical solutions: This invention provides a manufacturing process for a plastic magnetic pump body for electrolyte delivery, comprising the following steps: Step 1: Nitrogen-doped carbon-coated carbon nanotubes are ball-milled to obtain pretreated nitrogen-doped carbon-coated carbon nanotubes. Polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder are placed in a high-speed mixer and mixed evenly to obtain a composite molding material. At the same time, the surface of the metal skeleton is sandblasted and roughened, and anchoring through holes are opened. The surface of the inlet and outlet flange inserts is sandblasted and roughened. The metal skeleton and flange inserts are cleaned, dried, preheated, and fixed in the corresponding cavity of the mold. The composite molding material is then filled into the mold and cold-pressed to obtain a cold-pressed blank with a metal skeleton.

[0007] The specific process of ball milling is as follows: Nitrogen-doped carbon-coated carbon nanotubes and anhydrous ethanol were placed in a reaction vessel at a mass ratio of 1:10 and ultrasonically dispersed for 30-60 min. The mixture was then transferred to a planetary ball mill, and zirconium oxide grinding balls were added at a ball-to-material ratio of 8:1. The mixture was ball-milled for 1-2 h, centrifuged, washed, and vacuum-dried to constant weight to obtain pretreated nitrogen-doped carbon-coated carbon nanotubes.

[0008] The mass ratio of polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder is 100:2-3:15-25.

[0009] The pressure for cold pressing is 40-50 MPa, and the time is 4-6 minutes.

[0010] Step 2: Place the cold-pressed blank with metal skeleton in a sintering furnace, heat it to 370-380℃ at a heating rate of 20℃ / h and hold it at that temperature for sintering, then cool it to 280-300℃ at a rate of 15℃ / h for annealing, and then cool it to room temperature at a rate of 10℃ / h for demolding. Finally, the pump casing flow channel, flange sealing surface and threaded parts are precision machined to the design dimensions to obtain the pump body of the plastic magnetic pump for electrolyte transportation.

[0011] The holding and sintering time is 4-6 hours, and the annealing time is 2-3 hours.

[0012] Furthermore, the specific preparation process of nitrogen-doped carbon-coated carbon nanotubes is as follows: Polypyrrole-coated carbon nanotubes were placed in a tube furnace under nitrogen atmosphere protection, heated to 350-400℃ at 2℃ / min, and calcined for 60-90 min. Then, the temperature was increased to 650-700℃ at 5℃ / min and calcined for 1-2 h. After cooling to room temperature in the furnace, the product was washed with deionized water until the final washing solution was neutral, and then vacuum dried to constant weight to obtain nitrogen-doped carbon-coated carbon nanotubes.

[0013] Furthermore, the specific preparation process of polypyrrole-coated carbon nanotubes is as follows: Pyrrole and a 1 mol / L hydrochloric acid solution were placed in a reaction vessel and stirred at 25-35℃ for 10-20 min. Carbon nanotubes were added and ultrasonically dispersed for 20-40 min. Ammonium persulfate solution was slowly added at 0-5℃, and the reaction was continued at 25-35℃ for 1-2 h. The mixture was filtered, washed, vacuum dried to constant weight, ground, and sieved to obtain polypyrrole-coated carbon nanotubes.

[0014] The ratio of pyrrole, hydrochloric acid solution, carbon nanotubes and ammonium persulfate solution is 30-50g: 1-2L: 20-40g: 800-1200mL.

[0015] The ammonium persulfate solution is prepared by mixing ammonium persulfate and 1 mol / L hydrochloric acid, with a concentration of 35 g / L.

[0016] Furthermore, the specific preparation process of PFA-carbon fiber composite powder is as follows: The polyfluoroalkoxy resin and carbon fiber are melt-extruded in a twin-screw extruder, cooled and pelletized, and the pellets are crushed, ground and sieved in a high-speed pulverizer to obtain PFA-carbon fiber composite powder.

[0017] The mass ratio of polytetrafluoroalkoxy resin to carbon fiber is 3-4:1.

[0018] The twin-screw extruder has a processing temperature range of 330-340℃, 340-350℃, 350-360℃, and 360-370℃, a die temperature of 355-365℃, and a screw speed of 100-200 r / min.

[0019] The beneficial effects of this invention are: 1. The pump body of the plastic magnetic pump for electrolyte delivery prepared in this invention uses polytetrafluoroethylene (PTFE) as a corrosion-resistant matrix. Through the synergistic introduction of nitrogen-doped carbon nanotubes and PFA-carbon fiber composite powder, the antistatic properties and mechanical reinforcement of the material are improved while maintaining its resistance to electrolyte corrosion. Specifically, the nitrogen-doped carbon nanotubes are dispersed in the PTFE matrix after liquid-phase ball milling pretreatment, forming continuous conductive channels. The carbon fibers in the PFA-carbon fiber composite powder bear the main mechanical load, improving the load-bearing capacity of the matrix. Simultaneously, the PFA component softens and melts at the sintering temperature, helping to fill the gaps between PTFE particles and improve the density of the sintered green body. The synergistic effect of these two components gives the pump body both electrostatic discharge capability and structural load-bearing capacity.

[0020] 2. In the production process of the plastic magnetic pump body for electrolyte transportation, the nitrogen-doped carbon-coated carbon nanotubes, after liquid-phase ball milling pretreatment, are relatively uniformly dispersed when mixed with PTFE micropowder. This reduces the flying loss and soft agglomeration that easily occur when nano-sized powders are directly dry-mixed, thus improving the mixing consistency in industrial production. The PFA-carbon fiber composite powder is added in premixed particle form, with the carbon fiber pre-coated by PFA. When mixed with PTFE micropowder, this reduces uneven distribution caused by density differences and fiber entanglement, improving the packing uniformity of the composite molding material and the density consistency of the cold-pressed preform. This process route uses conventional PTFE cold-pressing molding and sintering equipment to produce thick-walled pump bodies that combine antistatic properties, corrosion resistance, and mechanical reinforcement, meeting the requirements for structural integrity and long-term operational reliability for safe electrolyte transportation. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1: This example provides a manufacturing process for a plastic magnetic pump body for electrolyte delivery, including the following steps: S1: Place 30g of pyrrole and 1L of 1mol / L hydrochloric acid solution in a reaction vessel, stir at 200r / min for 10min at 25℃, add 20g of carbon nanotubes, ultrasonically disperse for 20min, slowly add 800mL of 35g / L ammonium persulfate solution (prepared from ammonium persulfate and 1mol / L hydrochloric acid) at 0℃, continue the reaction at 200r / min for 1h at 25℃. After the reaction is completed, filter, wash the filter cake twice with deionized water, vacuum dry at 80℃ to constant weight, grind and sieve through a 200-mesh sieve to obtain polypyrrole-coated carbon nanotubes.

[0023] This step uses pyrrole as a monomer and ammonium persulfate as an oxidant. In an acidic medium provided by hydrochloric acid, the pyrrole monomer undergoes an oxidative polymerization reaction on the surface of carbon nanotubes. The resulting polypyrrole molecular chains coat the surface of the carbon nanotubes, forming a polypyrrole coating layer, thus obtaining polypyrrole-coated carbon nanotubes.

[0024] S2: Polypyrrole-coated carbon nanotubes were placed in a tube furnace under nitrogen atmosphere protection, heated to 350℃ at 2℃ / min, held for 60 min, then heated to 650℃ at 5℃ / min, held for 1 h, cooled to room temperature with the furnace, washed with deionized water until the last washing solution was neutral, and vacuum dried at 80℃ to constant weight to obtain nitrogen-doped carbon-coated carbon nanotubes.

[0025] This step uses polypyrrole-coated carbon nanotubes as a precursor and involves two-stage high-temperature calcination under nitrogen protection. The first stage of calcination causes the polypyrrole to undergo thermal decomposition and pre-carbonization, removing volatile small molecules and forming cross-linked carbon intermediates. The second stage of calcination promotes the deep carbonization of polypyrrole, and the nitrogen atoms in the polypyrrole are retained in the carbonization product to form a nitrogen-doped carbon coating layer, thus obtaining nitrogen-doped carbon-coated carbon nanotubes.

[0026] S3: Polyperfluoroalkoxy resin (PFA) and carbon fiber are added to a twin-screw extruder at a mass ratio of 3:1 for melt extrusion. The processing temperature of the twin-screw extruder is 330℃, 340℃, 350℃, and 360℃, the die temperature is 355℃, and the screw speed is 100r / min. After the material is melt-blended and extruded, it is cooled and pelletized. The pellets are placed in a high-speed pulverizer and crushed at 8000r / min for 1min. After grinding, the powder is sieved through a 200-mesh sieve to obtain PFA-carbon fiber composite powder.

[0027] S4: Nitrogen-doped carbon-coated carbon nanotubes and anhydrous ethanol were placed in a reaction vessel at a mass ratio of 1:10 and ultrasonically dispersed for 30 min. The mixture was then transferred to a planetary ball mill, and zirconium oxide grinding balls were added at a ball-to-material ratio of 8:1. The mixture was ball-milled at 200 r / min for 1 h. The supernatant was removed by centrifugation, and the solid was washed twice with anhydrous ethanol by centrifugation. The solid was collected and vacuum dried at 60 °C to constant weight to obtain pretreated nitrogen-doped carbon-coated carbon nanotubes.

[0028] S5: Polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder are mixed uniformly in a high-speed mixer at a mass ratio of 100:2:15 to obtain a composite molding material. At the same time, the surface of the metal skeleton (316L stainless steel) is roughened by sandblasting and anchoring through holes are opened. The surface of the inlet and outlet flange inserts is roughened by sandblasting. The above metal skeleton and flange inserts are cleaned with acetone, dried, and preheated to 80°C. They are then fixed in the corresponding cavity of the mold. The composite molding material is filled into the mold and a pressure of 40MPa is applied for cold pressing. The cold pressing time is 4 minutes to obtain a cold-pressed blank with a metal skeleton.

[0029] S6: The cold-pressed blank with a metal skeleton is placed in a sintering furnace, heated to 370°C at a heating rate of 20°C / h and held for sintering for 4 hours. Then it is cooled to 280°C at a rate of 15°C / h and held for 2 hours for annealing. Finally, it is cooled to room temperature at a rate of 10°C / h for demolding. The pump casing flow channel, flange sealing surface and threaded parts are then precision machined to the design dimensions to obtain the pump body of the plastic magnetic pump for electrolyte transportation.

[0030] Example 2: This example provides a manufacturing process for a plastic magnetic pump body for electrolyte delivery, including the following steps: S1: Place 40g of pyrrole and 1.5L of 1mol / L hydrochloric acid solution in a reaction vessel, stir at 250r / min for 15min at 30℃, add 30g of carbon nanotubes, ultrasonically disperse for 30min, slowly add 1000mL of 35g / L ammonium persulfate solution (prepared from ammonium persulfate and 1mol / L hydrochloric acid) at 3℃, and continue the reaction at 250r / min at 30℃ for 1.5h. After the reaction is completed, filter, wash the filter cake three times with deionized water, vacuum dry at 90℃ to constant weight, grind and sieve through a 250-mesh sieve to obtain polypyrrole-coated carbon nanotubes.

[0031] S2: Polypyrrole-coated carbon nanotubes were placed in a tube furnace under nitrogen atmosphere protection, heated to 380℃ at 2℃ / min, held for 75 min, then heated to 680℃ at 5℃ / min, held for 1.5 h, cooled to room temperature with the furnace, washed with deionized water until the last washing solution was neutral, and vacuum dried at 90℃ to constant weight to obtain nitrogen-doped carbon-coated carbon nanotubes.

[0032] S3: Polyperfluoroalkoxy resin (PFA) and carbon fiber are added to a twin-screw extruder at a mass ratio of 3.5:1 for melt extrusion. The processing temperature of the twin-screw extruder is 335℃, 345℃, 355℃, and 365℃, the die temperature is 360℃, and the screw speed is 150r / min. After the material is melt-blended and extruded, it is cooled and pelletized. The pellets are placed in a high-speed pulverizer and crushed at 10000r / min for 2min. After grinding, the powder is sieved through a 300-mesh sieve to obtain PFA-carbon fiber composite powder.

[0033] S4: Nitrogen-doped carbon-coated carbon nanotubes and anhydrous ethanol were placed in a reaction vessel at a mass ratio of 1:10 and ultrasonically dispersed for 45 min. The mixture was then transferred to a planetary ball mill, and zirconium oxide grinding balls were added at a ball-to-material ratio of 8:1. The mixture was ball-milled at 250 r / min for 1.5 h. The supernatant was removed by centrifugation, and the mixture was washed three times with anhydrous ethanol by centrifugation. The solid was collected and vacuum dried at 70 °C to constant weight to obtain pretreated nitrogen-doped carbon-coated carbon nanotubes.

[0034] S5: Polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder are mixed uniformly in a high-speed mixer at a mass ratio of 100:2.5:20 to obtain a composite molding material. At the same time, the surface of the metal skeleton (316L stainless steel) is roughened by sandblasting and anchoring through holes are opened. The surface of the inlet and outlet flange inserts is roughened by sandblasting. The metal skeleton and flange inserts are cleaned with acetone, dried, and preheated to 90°C. They are then fixed in the corresponding cavity of the mold. The composite molding material is filled into the mold and a pressure of 45MPa is applied for cold pressing. The cold pressing time is 5 minutes to obtain a cold-pressed blank with a metal skeleton.

[0035] S6: The cold-pressed blank with a metal skeleton is placed in a sintering furnace, heated to 375°C at a heating rate of 20°C / h and held for sintering for 5 hours. Then it is cooled to 290°C at a rate of 15°C / h and held for 2.5 hours for annealing. Then it is cooled to room temperature at a rate of 10°C / h for demolding. Finally, the pump casing flow channel, flange sealing surface and threaded parts are precision machined to the design dimensions to obtain the pump body of the plastic magnetic pump for electrolyte transportation.

[0036] Example 3: This example provides a manufacturing process for a plastic magnetic pump body for electrolyte delivery, including the following steps: S1: Place 50g of pyrrole and 2L of 1mol / L hydrochloric acid solution in a reaction vessel, stir at 300r / min for 20min at 35℃, add 40g of carbon nanotubes, ultrasonically disperse for 40min, slowly add 1200mL of 35g / L ammonium persulfate solution (prepared from ammonium persulfate and 1mol / L hydrochloric acid) at 5℃, and continue the reaction at 300r / min for 2h at 35℃. After the reaction is completed, filter, wash the filter cake 4 times with deionized water, vacuum dry at 100℃ to constant weight, grind and sieve through a 300-mesh sieve to obtain polypyrrole-coated carbon nanotubes.

[0037] S2: Polypyrrole-coated carbon nanotubes were placed in a tube furnace under nitrogen atmosphere protection, heated to 400℃ at 2℃ / min, held for 90min, then heated to 700℃ at 5℃ / min, held for 2h, cooled to room temperature with the furnace, washed with deionized water until the last washing solution was neutral, and vacuum dried at 100℃ to constant weight to obtain nitrogen-doped carbon-coated carbon nanotubes.

[0038] S3: Polyperfluoroalkoxy resin (PFA) and carbon fiber are added to a twin-screw extruder at a mass ratio of 4:1 for melt extrusion. The processing temperature of the twin-screw extruder is 340℃, 350℃, 360℃, and 370℃, the die temperature is 365℃, and the screw speed is 200r / min. After the material is melt-blended and extruded, it is cooled and pelletized. The pellets are placed in a high-speed pulverizer and crushed at 12000r / min for 3 minutes. After grinding, the powder is sieved through a 400-mesh sieve to obtain PFA-carbon fiber composite powder.

[0039] S4: Nitrogen-doped carbon-coated carbon nanotubes and anhydrous ethanol were placed in a reaction vessel at a mass ratio of 1:10 and ultrasonically dispersed for 60 min. The mixture was then transferred to a planetary ball mill, and zirconium oxide grinding balls were added at a ball-to-material ratio of 8:1. The mixture was ball-milled at 300 r / min for 2 h. The supernatant was removed by centrifugation, and the mixture was washed four times with anhydrous ethanol by centrifugation. The solid was collected and vacuum dried at 80 °C to constant weight to obtain pretreated nitrogen-doped carbon-coated carbon nanotubes.

[0040] S5: Polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder are mixed uniformly in a high-speed mixer at a mass ratio of 100:3:25 to obtain a composite molding material. At the same time, the surface of the metal skeleton (316L stainless steel) is roughened by sandblasting and anchoring through holes are opened. The surface of the inlet and outlet flange inserts is roughened by sandblasting. The metal skeleton and flange inserts are cleaned with acetone, dried, and preheated to 100°C. They are then fixed in the corresponding cavity of the mold. The composite molding material is filled into the mold and a pressure of 50MPa is applied for cold pressing. The cold pressing time is 6 minutes to obtain a cold-pressed blank with a metal skeleton.

[0041] S6: The cold-pressed blank with a metal skeleton is placed in a sintering furnace, heated to 380°C at a heating rate of 20°C / h and held for sintering for 6 hours. Then it is cooled to 300°C at a rate of 15°C / h and held for 3 hours for annealing. Then it is cooled to room temperature at a rate of 10°C / h for demolding. Finally, the pump casing flow channel, flange sealing surface and threaded parts are precision machined to the design dimensions to obtain the pump body of the plastic magnetic pump for electrolyte transportation.

[0042] Comparative Example 1: The difference from Example 2 is that in step S4, commercially available carbon nanotubes of equal mass are used instead of the nitrogen-doped carbon-coated carbon nanotubes prepared in step S2, and ball milling dispersion pretreatment is performed in the same way as in step S4 to obtain pretreated commercially available carbon nanotubes; in step S5, the pretreated commercially available carbon nanotubes are used instead of the pretreated nitrogen-doped carbon-coated carbon nanotubes, and the remaining components and steps remain unchanged to obtain the composite molding material.

[0043] Comparative Example 2: The difference from Example 2 is that step S3 is omitted. In step S5, when preparing the composite molding material, polyperfluoroalkoxy resin powder and carbon fiber are added to a high-speed mixer at a mass ratio of 3.5:1. PFA-carbon fiber composite powder is not prepared in advance. The remaining components and steps remain unchanged to obtain the composite molding material.

[0044] Comparative Example 3: The difference from Example 2 is that, in step S5, when preparing the composite molding material, no pretreated nitrogen-doped carbon-coated carbon nanotubes are added, and an equal mass of polytetrafluoroethylene micro powder is used to make up the difference. The remaining components and steps remain unchanged to obtain the composite molding material.

[0045] Comparative Example 4: The difference from Example 2 is that, in step S5, when preparing the composite molding material, PFA-carbon fiber composite powder is not added, and the amount is supplemented with an equal mass of polytetrafluoroethylene micro powder. The remaining components and steps remain unchanged to obtain the composite molding material.

[0046] Comparative Example 5: The difference from Example 2 is that step S4 is not performed. In step S5, when preparing the composite molding material, the nitrogen-doped carbon-coated carbon nanotubes prepared in step S2 are directly added to the high-speed mixer without ball milling dispersion pretreatment. The remaining components and steps remain unchanged to obtain the composite molding material.

[0047] The carbon nanotubes purchased in the above embodiments and comparative examples are multi-walled carbon nanotubes produced by Qingdao Haoxin New Energy Technology Co., Ltd., with an outer diameter of 10-30 nm and a length of 5-20 μm; the polytetrafluoroalkoxy resin (PFA) is produced by DuPont, with the brand name Teflon PFA 340; the polytetrafluoroethylene micro powder is produced by Shandong Dongyue Polymer Materials Co., Ltd., with an average particle size of 25-35 μm; and the carbon fiber is produced by Jiangsu Hengshen Co., Ltd., and is short-cut carbon fiber with a short-cut length of 3-6 mm.

[0048] Sample preparation: The composite molding materials obtained in step S5 of Examples 1-3 were cold-pressed and sintered in standard molds without metal skeletons and flange inserts according to the process parameters in steps S5 and S6 of the corresponding examples to obtain block samples.

[0049] The composite molding materials obtained from Comparative Examples 1 to 5 were cold-pressed and sintered in standard molds without metal skeletons and flange inserts, with reference to the process parameters of steps S5 and S6 in Example 2, to obtain block samples.

[0050] The above-mentioned samples and the pump body matrix prepared in the corresponding embodiments are consistent in terms of formulation composition, cold-pressed blank density and sintering crystallization degree, and their performance test results can represent the performance of the pump body plastic matrix.

[0051] The samples prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and the test results are shown in Table 1: Tensile strength test: Referring to standard GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", the above block specimens were processed into standard tensile specimens and tested using a universal electronic tensile testing machine. The tensile strength and elongation at break of the material were recorded.

[0052] Surface resistivity test: Referring to standard GB / T 1410-2006 "Test methods for volume resistivity and surface resistivity of solid insulating materials", the above block sample was processed into a flat plate sample of 100mm×100mm×4mm. The surface resistance was measured by a high resistance meter using the three-electrode method under an applied voltage of 500V, and converted into surface resistivity according to the electrode size specified in the standard.

[0053] Corrosion resistance treatment: Lithium hexafluorophosphate (LiPF6) was dissolved in a solvent containing ethylene carbonate (EC) and dimethyl carbonate (DMC) at a volume ratio of 1:1 to prepare a simulated electrolyte with a concentration of 1 mol / L. The plate sample after the surface resistivity test was placed in the simulated electrolyte and soaked at 60°C for 7 days. After removal, it was rinsed with deionized water and vacuum dried at 80°C to constant weight. The sample was then conditioned in an environment with a temperature of (23±2)°C and a relative humidity of (50±5)% for 24 hours. The surface resistivity of the corrosion-treated sample was tested again and its surface resistivity was recorded.

[0054] Table 1 Performance Test Table of Plastic Magnetic Pump Body for Electrolyte Delivery As shown in Table 1, the tensile strength, elongation at break, and surface resistivity of the plastic matrix of the pump body for electrolyte transportation prepared in Examples 1-3 are all within a reasonable range. Moreover, the surface resistivity remains within the antistatic safety range after simulated electrolyte corrosion treatment. This indicates that the present invention constructs an antistatic conductive network in the PTFE matrix by coating carbon nanotubes with nitrogen-doped carbon, and uses PFA-carbon fiber composite powder to provide structural reinforcement and sintering aid. PFA softens and melts at the sintering temperature, which helps to improve the interfacial bonding between PTFE particles and the density of the matrix. Carbon fiber bears the main load and inhibits the cold flow deformation of the matrix. At the same time, the perfluorinated system maintains the corrosion resistance continuity of the PTFE matrix, meeting the comprehensive requirements of structural integrity and electrostatic discharge reliability for safe electrolyte transportation.

[0055] In Comparative Example 1, the tensile strength and elongation at break were significantly reduced, the surface resistivity was significantly increased, and the corrosion caused substantial degradation. This may be because commercially available carbon nanotubes are not modified with a polypyrrole-derived nitrogen-doped carbon coating layer, making them prone to agglomeration during liquid-phase dispersion and subsequent mixing. This prevents the formation of a uniformly dispersed conductive network in the PTFE matrix, leading to stress concentration and discontinuous electrostatic discharge channels. After corrosion, the agglomerate interface easily becomes an electrolyte penetration channel, further damaging the conductive network and significantly reducing the long-term antistatic effect.

[0056] In Comparative Example 2, the tensile strength and elongation at break decreased, while the surface resistivity increased. This may be because the polyfluoroalkoxy resin and carbon fiber were added directly without premixing, and the two were dispersed separately in the PTFE powder. The carbon fiber was prone to local agglomeration, and the sintering aid and bonding effect of PFA could not be uniformly exerted, resulting in a decrease in matrix density and a reduction in mechanical load-bearing efficiency. At the same time, the uneven dispersion of carbon fiber resulted in a disordered distribution of the conductive phase, making it difficult to form an effective spatial complementary conductive network with the nitrogen-doped carbon-coated carbon nanotubes. The resistivity stability was insufficient, and after corrosion, the electrolyte penetration at the interfacial gaps intensified, leading to a significant increase in resistivity.

[0057] The surface resistivity in Comparative Example 3 exceeded the antistatic safety range, and the tensile strength was also lower than that in the Example. This may be because after completely removing nitrogen-doped carbon-coated carbon nanotubes from the system, the carbon fibers in the PFA-carbon fiber composite powder alone could not form a continuous and stable antistatic conductive network at low content, and static charge could not be effectively discharged; at the same time, the lack of nanoscale conductive fillers to fill the matrix microstructure and the synergistic reinforcement effect with carbon fibers resulted in the overall mechanical properties failing to reach the level of the Example.

[0058] In Comparative Example 4, the tensile strength of the pump body plastic matrix was significantly reduced, while the elongation at break was significantly increased. Although the surface resistivity was within the antistatic range, the value was relatively high. This may be because after removing the PFA-carbon fiber composite powder from the system, the PTFE matrix lacked a carbon fiber reinforcing phase, resulting in a significant decrease in load-bearing capacity and creep resistance. At the same time, the reduction of PFA weakened the interparticle diffusion bonding effect during sintering, reducing the matrix density. The antistatic performance was maintained solely by nitrogen-doped carbon-coated carbon nanotubes, but the lack of macroscopic conductive channels from carbon fibers resulted in insufficient network continuity, higher resistivity, and lower stability compared to the examples.

[0059] In Comparative Example 5, the pump body plastic matrix exhibited the lowest tensile strength and elongation at break, with a surface resistivity far exceeding the antistatic safety threshold. This may be because the nitrogen-doped carbon-coated carbon nanotubes, without liquid-phase ball milling dispersion pretreatment, existed as severely aggregated particles in the PTFE matrix, failing to form a uniform and continuous conductive network, resulting in highly unstable electrostatic discharge. Simultaneously, these rigid aggregates created significant stress concentration points in the matrix, easily inducing microcracks during cold pressing and sintering shrinkage, leading to substantial deterioration of mechanical properties. Furthermore, after corrosion, the interface between the aggregates and PTFE was easily penetrated and destroyed by the electrolyte, further degrading the conductive network. This indicates that ball milling dispersion pretreatment is a crucial process step to ensure uniform dispersion of nanofillers and achieve synergistic improvement in antistatic and mechanical properties.

[0060] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. The manufacturing process of the pump body for a plastic magnetic pump used for electrolyte delivery, characterized in that, Includes the following steps: Step 1: Nitrogen-doped carbon-coated carbon nanotubes are ball-milled to obtain pretreated nitrogen-doped carbon-coated carbon nanotubes. Polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder are placed in a high-speed mixer and mixed evenly to obtain composite molding material. At the same time, the surface of the metal skeleton is sandblasted and roughened and anchoring through holes are opened. The surface of the inlet and outlet flange inserts is sandblasted and roughened. The metal skeleton and flange inserts are cleaned, dried, preheated, and fixed in the corresponding cavity of the mold. The composite molding material is then filled into the mold and cold-pressed to obtain a cold-pressed blank with a metal skeleton. Step 2: Place the cold-pressed blank with metal skeleton in a sintering furnace, heat it to 370-380℃ at a heating rate of 20℃ / h and hold it at that temperature for sintering, then cool it to 280-300℃ at a rate of 15℃ / h for annealing, and then cool it to room temperature at a rate of 10℃ / h for demolding. Finally, the pump casing flow channel, flange sealing surface and threaded parts are precision machined to the design dimensions to obtain the pump body of the plastic magnetic pump for electrolyte transportation.

2. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 1, characterized in that, The specific process of ball milling described in step one is as follows: Nitrogen-doped carbon-coated carbon nanotubes and anhydrous ethanol were placed in a reaction vessel at a mass ratio of 1:10 and ultrasonically dispersed for 30-60 minutes. The mixture was then transferred to a planetary ball mill, and zirconium oxide grinding balls were added at a ball-to-material ratio of 8:

1. The mixture was ball-milled for 1-2 hours, centrifuged, washed, and then vacuum-dried to constant weight.

3. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 1, characterized in that, The pressure for cold pressing in step one is 40-50 MPa, and the time is 4-6 min.

4. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 1, characterized in that, The mass ratio of polytetrafluoroethylene micro powder, pretreated nitrogen-doped carbon-coated carbon nanotubes, and PFA-carbon fiber composite powder in step one is 100:2-3:15-25.

5. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 4, characterized in that, The specific preparation process of the nitrogen-doped carbon-coated carbon nanotubes is as follows: Polypyrrole-coated carbon nanotubes were placed in a tube furnace under nitrogen atmosphere protection, heated to 350-400℃ at 2℃ / min, and calcined for 60-90 min. Then, the temperature was increased to 650-700℃ at 5℃ / min and calcined for 1-2 h. After cooling to room temperature in the furnace, the product was washed with deionized water until the final washing solution was neutral, and then vacuum dried to constant weight to obtain nitrogen-doped carbon-coated carbon nanotubes.

6. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 5, characterized in that, The specific preparation process of the polypyrrole-coated carbon nanotubes is as follows: Pyrrole and a 1 mol / L hydrochloric acid solution were placed in a reaction vessel and stirred at 25-35℃ for 10-20 min. Carbon nanotubes were added and ultrasonically dispersed for 20-40 min. Ammonium persulfate solution was slowly added at 0-5℃, and the reaction was continued at 25-35℃ for 1-2 h. The mixture was filtered, washed, vacuum dried to constant weight, ground, and sieved to obtain polypyrrole-coated carbon nanotubes.

7. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 5, characterized in that, The ratio of pyrrole, hydrochloric acid solution, carbon nanotubes and ammonium persulfate solution is 30-50g: 1-2L: 20-40g: 800-1200mL; The ammonium persulfate solution is prepared by mixing ammonium persulfate and hydrochloric acid with a concentration of 1 mol / L, and the concentration is 35 g / L.

8. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 4, characterized in that, The specific preparation process of the PFA-carbon fiber composite powder is as follows: PFA-carbon fiber composite powder is obtained by melt extrusion of polyperfluoroalkoxy resin and carbon fiber in a twin-screw extruder, cooling and pelletizing, crushing, grinding and sieving the pellets in a high-speed pulverizer. The mass ratio of the polyfluoroalkoxy resin to the carbon fiber is 3-4:

1.

9. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 8, characterized in that, The twin-screw extruder has a processing temperature range of 330-340℃, 340-350℃, 350-360℃, and 360-370℃, a die temperature of 355-365℃, and a screw speed of 100-200 r / min.

10. The manufacturing process of the plastic magnetic pump body for electrolyte delivery according to claim 1, characterized in that, The sintering time in step two is 4-6 hours, and the annealing time is 2-3 hours.